Media Massa Serambi Indonesia: Antara Industri Dan Idealisme - Nurdin, Hanifah; Kholil, Syukur (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2023)
Serambi Indonesia is one of the major mass media in Aceh. Almost all information is reported by Serambi. Since its establishment in 1989 until now Serambi Indonesia has continued to experience developments in running its industry. Serambi Indonesia also publishes news that occurs around Aceh, the news that is revealed has gone through a selection process by the editor so that it becomes news that is suitable for public consumption. To get data on how Serambi Indonesia can survive between idealism and industry, researchers use descriptive research methods with a qualitative approach. The research technique is purposive sampling by conducting observations, interviews in obtaining data. Primary data is obtained from company leaders, advertising managers and journalists, while secondary data from various existing literature. The theory used in this research is management theory which is better known as POAC (planning, organizing, actuating, controlling). The results of the study found that Serambi carries a balanced concept between Industry and Idealism. Serambi Indonesia cannot impose or be too idealistic to maintain its industry. Because Serambi Indonesia has employees who depend on the company and capital owners who want the benefits of the capital provided. Serambi Indonesia strives to prioritize the need for information to the public and does not put aside the information needs of the public and package it well and polite language so as not to clash with institutions or the government.